Early Expression of Functional Markers on CD4+ T Cells Predicts Outcomes in ICU Patients With Sepsis - Chen, Jianwei; Wang, Hao; Guo, Ran; Li, Haolong; Cui, Na (Frontiers in Immunology, 2022)
Objective: There is evidence that metabolic disorder, dysfunction and abnormal apoptosis of immune cells are closely related to immunosuppression in sepsis. Single monitoring of exhaustion receptors does not reflect well the immune status of septic patients; therefore, we monitored immune status in relation to metabolism, function and apoptosis of immune cells to find good prognostic indicators for sepsis. Design: A single-center prospective observational study. Setting: Teaching hospital including an academic tertiary care center. Patients: 81 patients with sepsis and 22 without sepsis admitted to the ICU. Interventions: Patients were divided according to Sequential Organ Failure Assessment (SOFA) score: mild sepsis 2–5 points and severe sepsis ≥6 points. SOFA score was recalculated daily. If it changed by ≥2 points, T-cell metabolism, function and apoptotic makers [mechanistic target of rapamycin (mTOR), T-bet, interferon (IFN)-γ, granzyme B, and programmed cell death (PD)-1] were continuously monitored on days 1, 3 and 5 after admission. Measurements and Main Results: The overall status of immune cells was compared among patients with different severity of sepsis. Patients with severe sepsis, compared with mild and no sepsis, had lower lymphocyte counts, higher expression of receptors associated with cell metabolism, activation and apoptosis, and lower expression of functional receptors. Multivariate regression analysis revealed that frequency of CD4+ T cells expressing mTOR, IFN-γ and PD-1 at admission was an independent predictor of 28-day mortality. Receiver operating characteristic curve analysis indicated that frequency of CD4+ T cells expressing mTOR, IFN-γ and PD-1 predicted 28-day mortality, with cutoffs of 30.57%, 12.81% and 22.46%, respectively. Conclusions: Abnormally increased expression of metabolic and apoptotic receptors on CD4+ T cells and decreased expression of functional factors are associated with poor prognosis in ICU patients with sepsis. Poor prognosis can be identified by early detection of expression of mTOR, IFN-γ and PD-1 on CD4+ T cells.